COMPLIMENTS BY MALE AND FEMALE CHARACTERS IN ME BEFORE YOU MOVIE - Widyanita, Citra Yudha; Pasaribu, Truly Almendo (Universitas Swadaya Gunung Jati, 2019)
Compliments are common in daily communication as they serve to build solidarity. They are given within speech communities depending on the extra-linguistic factors, such as gender and the relationship among the speakers. The current research focuses on how male and female characters in the movie ?Me Before You? express compliments. This study elaborates real examples on how compliments are used to serve particular social functions. This research employed a descriptive qualitative method in analyzing the data from the subtitle of ?Me Before You? movie using a framework by Herbert, Manes, and Wolfson. The researcher found there were four compliment functions that were used by male and female characters in the movie, namely expressing admiration, solidarity, conversation strategy and reinforced desired behavior. However, in the movie, we did not find the compliments to replace other speech acts and soften criticisms as the language used in the movie is highly influenced by the main characters that tend to be straight forward. The use of compliments is highly affected by the traits of the characters and the plot narrating how the lead male character undergoes the transitions to be a better person.